INFORMATION CONTENT OF VECTOR RADIOTHERMAL FIELDS IN THE PROBLEM OF CORRELATION-EXTREMAL NAVIGATION OF AIRCRAFT - V. I. Troitsky (Научный вестник МГТУ ГА)
Various informative characteristics of radio thermal fields for generating the standard images in correlation-extremal navigation systems are considered as components of a vector field. Some properties of such space-time fields are described.